Prevelance and factors contributing to anemia among pregnancy women in Hospital Universiti Sains Malaysia (HUSM) - Abdullah, Norazila (Universiti Sains Malaysia, 2009)
Anemia is one of the most frequent complications related to pregnancy. Anemia is defined as a decrease in hemoglobin in the blood to a level below the normal range of 10-11 g/dL for pregnancy women. Anemia also can cause many complications which can effects maternal and child health. Many factors can contribute to anemia during pregnancy such as level of education, income, interval of pregnancy, nutritional intake and others. Therefore, the purposes of the study were to identify the prevalence of anemia among pregnancy women, to determine association between anemia with the nutrient intake, selected socio-demographic data and interval of pregnancy among pregnancy women. The study design is cross sectional study. The study had been conducted in O&G clinic and antenatal wards in HUSM. The numbers of respondents involved in the study were 55 respondents. The subjects were selected using convenience sampling. The associations between income, level of education, and interval of pregnancy with anemia were determined by using chi-square test where p value will be determined. While, the prevalence of anemia among pregnancy women was described in percentage. The results showed the prevalence of anemia among pregnancy women in HUSM was 18.2%. Approximately, 10 respondents was having anemia from the total of 55 respondents involved. There was no association found between anemia and income where p value was 0.23(p>0.001). The result showed majority of the respondents 8(14.5%) whose having anemia has income between RM2000-RM3000. There was also no association found between anemia and level of education where p value was 0.18 (p>0.001 ). Respondents who's mostly getting anemia were respondents with higher education 7(12.7%). A part from that, no association was found between anemia and interval of pregnancy where p value was 0.73(p>0.001). Women who have interval of pregnancy less than 2 years have a tendency to get anemia 6(10.9%) compared to mothers with interval of pregnancy more than 2 years. But, there was an association was found between anemia and nutritional intake where p value was O.00 (p<0.001). As a conclusion, nutritional intake was one of the important factors contributing to anemia during pregnancy.